The Relationship Between Maternal Knowledge and Attitude Towards Stunting Prevention Efforts and the Incidence of Stunting in Toddlers - Dwista Anggraeni, Dinda; sri mulyanti; Budiawan, Heri; Handayani, Hani (HealthCare Nursing Journal, 2025)
Stunting is a condition of impaired physical and cognitive growth due to malnutrition during the growth period. Children who are stunted can experience disruptions in physical, mental, cognitive, and intellectual development, making them unable to learn optimally. The aim of the research is to determine the relationship between maternal knowledge and attitudes towards stunting prevention efforts and the incidence of stunting in toddlers. The research method is quantitative with a correlational research design using a cross-sectional approach. The population consists of all mothers with toddlers in the working area of the Cigeureung Health Center in Tasikmalaya City, with proportional random sampling yielding a total of 94 samples. Data were analyzed using frequency distribution and chi-square test. The research results showed that the majority of toddlers experienced stunting, with 54 toddlers (57.4%), the majority of mothers had low knowledge, with 67 respondents (71.3%), and negative maternal attitudes, with 55 respondents (58.5%). The results of the Chi-square test for knowledge showed that there is a significant relationship between mothers' knowledge and attitudes about stunting prevention efforts and the incidence of stunting in toddlers. Based on the research results, it is recommended to conduct health education regularly and on schedule to improve mothers' knowledge and attitudes about stunting prevention efforts, especially for mothers with toddlers, by implementing health promotion methods in both small and large groups.